Assessing readiness on blended learning among lecturers in UiTM Merbok / Nor Fatihah Roslan - Roslan, Nor Fatihah (2014)
Research has found that blended courses have the potential to increase student learning outcomes while lowering attrition rates in comparison with equivalent fully online courses (Dzuiban, Hartman & Moskal, 2004). This study reports the readiness on blended learning among lecturers in MARA University of Technology. Many higher learning institutions in Malaysia have implemented blended learning because of its effectiveness as a learning approach. However, studies have shown that academicians are apprehensive about teaching in blended learning due to several factors. Four factors representing independent variables that contribute to the attitude and readiness with the blended learning. Data are gathered through surveys among lecturers in one of the MARA University Technology branches in Kedah which implemented blended learning. Among the factors which influenced the readiness on blended learning are perceived usefulness of the system, facilities, knowledge and educational technology preference. Findings from this study provided insights on the attitude towards the readiness on blended learning. Its practical contribution includes knowledge which can be incorporated into the blended learning training modules to address the problem of low readiness le el on blended learning.